HUBUNGAN RIWAYAT DIABETES MELITUS DENGAN PENYAKIT GINJAL KRONIS DI RUANG PENYAKIT DALAM RSUD dr. M. YUNUS BENGKULU - Devi Listiana; Awal Isgiyanto; Icha Alvionita (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
This study aimed to study the association of history of diabetes mellitus with chronic kidney disease in Inner Disease Room RSUD dr. M. Yunus Bengkulu. This research used cross sectional design. The population in this study patients with kidney failure who were treated in the Inner Disease Room RSUD dr. M. Yunus Bengkulu, amounting to 142 patients. Sampling technique total sampling that was all patient of chronic kidney disease which was treated in Inner Disease Room RSUD dr. M. Yunus Bengkulu which amounted to 142 patients sampled. The data collection in this study used secondary data by looking at documentary records in the Inner Disease Room of dr. M. Yunus Bengkulu. Data analysis technique was done by using univariate and bivariate analysis with Chi-Square (χ2 ) statistic test through SPSS program.The results of the study were: from 142 patients, there were 74 patients (52.1%) with chronic kidney disease stage 5, 80 patients (56.3%) had a history of diabetes mellitus, there was a significant relationship between history of diabetes mellitus with chronic kidney disease in Inner Disease Room RSUD dr. M. Yunus Bengkulu with moderate relationship category, and patients with a history of diabetes mellitus have a risk 6 times compared of chronic kidney disease stage 5 with patients who have no history of diabetes mellitus. It was expected that health workers, especially nurses in order to provide more complete nursing care, especially in patients with chronic kidney disease.